Bubble Over the Head: Adeloye-Odeku Disease in a Turkish Child-Case Report - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2014)
Adeloye-Odeku disease is composed Of dermoid cyst over anterior fontanelle, first described in 1971. We present an 11-year-old girl with a soft, fluctuant swelling over bregma. The lesion content was isointense to cerebrospinal fluid on both T2W and FLAIRW images. There was a lytic area under the lesion, seen on CT. The lesion was totally excised. Histopathology confirmed the diagnosis. The case was unique; because a fibrous band was observed extending to superior sagittal sinus and it has never been reported before. Although lesions are sub-aponeurotic, because of this kind of fibrous band, a thorough examination with neuroimaging tools is very important for planning of surgery.
Keywords: Bregma; Anterior fontanelle; Dermoid cyst; Neuroimaging; Adeloye-Odeku disease; CONGENITAL DERMOID CYST; ANTERIOR FONTANELLE